Strategi Pengembangan Sumber Daya Manusia dalam Meningkatkan Kualitas Kinerja Karyawan di PT. PLN(Persero) UP3 Kota Parepare - Albad, Ghina Alvina Putri; Ramadani, Sahrul; Ilahi, Andi Alfianto Anugrah; Dinsar, Arfandy (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2024)
The study analyzes the human resource development strategy at PT. PLN (Persero) UP3 Kota Parepare and its impact on employee performance. Using a descriptive qualitative method, the study found that PT. PLN (Persero) UP3 Kota Parepare successfully implemented effective training such as On the Job Training (OJT) and Off the Job Training (Off-JT), which enhanced employees' skills and knowledge. This strategy improved productivity, efficiency, adaptability to changes, employee satisfaction, retention, and a positive work culture. In conclusion, the human resource development strategy at PT. PLN (Persero) UP3 Kota Parepare has improved employee performance and had a positive impact on the company. This strategy must continue to be implemented and adjusted to meet labor market needs to ensure optimal employee performance